Perancangan Sistem Online Food Ordering Berbasis Web Menggunakan Metode Agile - Ahmad Reza; Taupik Abdul Rahman (PT Jurnal Cendekia Indonesia, 2025)
The rapid development of information technology has significantly influenced various aspects of life, including the food and beverage industry. Online food ordering systems are now essential to improve transaction speed and convenience for both customers and business owners. This study aims to design a web-based food ordering system using the Agile methodology, which emphasizes iterative development, collaboration, and adaptability to changing user needs. The development process consists of six stages: planning, design, development, testing, deployment, and review. The system provides essential features such as user registration, food ordering, menu and order management, ticket support, and responsive web-based transaction reports. Testing was conducted across desktop and mobile platforms, as well as multiple browsers to ensure system compatibility. The results showed that the system operates effectively and meets user expectations. By implementing this system, food business operators—especially small to medium enterprises—can manage transactions more efficiently, reduce errors, and enhance customer satisfaction. This system is expected to be a practical digital solution that supports the transformation of the culinary business toward a more modern and integrated direction.